Comparative Reproduction Aspects of the Deep-water Shrimps Aristaeomorpha foliacea and Aristeus antennatus (Decapoda, Aristeidae) in the Greek Ionian Sea (Eastern Mediterranean) - Kapiris, K.; Thessalou-Legaki, M. (International Journal of Zoology, 2009)
In the eastern Ionian Sea, the deep-water shrimps Aristaeomorpha foliacea and Aristeus antennatus constitute a virgin fishing resource, since their maximum abundance depth exceeds commercial exploitation depths. The two sympatric species share a number of common reproductive features, such as summer reproduction. A slight temporal shift in mating activity, ovarian maturation, and spawning period was observed between species. The most notable difference was the more pronounced seasonality in reproductive activity of Aristeus antennatus compared to that of A. foliacea as evidenced by the frequency of inseminated females and functionally mature males, as well as by the shorter ovarian maturation period. Nevertheless, regarding the whole life span, both sexes of Aristeus antennatus exhibit a more extended reproductive activity in comparison to A. foliacea. No notable differentiation of both species existed in comparison to other Mediterranean regions.